Head first Rails - Griffiths, David, 1969- (Head first series., 2009)
Ready to transport your web applications into the Web 2.0 era? Head First Rails takes your programming -- and productivity -- to the max. You'll learn everything from the fundamentals of Rails scaffolding to building customized interactive web apps using Rails' rich set of tools and the MVC framework. Please note this book covers Rails 2. By the time you're finished, you'll have learned more than just another web framework. You'll master database interactions, integration with Ajax and XML, rich content, and even dynamic graphing of your data -- all in a fraction of the time it takes to build the same apps with Java, PHP, ASP.NET, or Perl. You'll even get comfortable and familiar with Ruby, the language that underpins Rails. But you'll do it in the context of web programming, and not through boring exercises such as "Hello, World!" Your time is way too valuable to waste struggling with new concepts. Using the latest research in cognitive science and learning theory to craft a multi-sensory learning experience, Head First Rails uses a visually rich format designed to take advantage of the way your brain really works